La protection au titre des monuments historiques des espaces liés à la gastronomie : l’exemple de la Bourgogne - Michaël Vottero (In Situ)
The Burgundy region is may be seen as a gastronomic region par excellence and today it has a certain number of buildings which are associated with this theme and which are protected under the terms of French legislation on historic monuments. For over forty years now, the region’s historic monuments conservation service has carried out several campaigns of statutory protection on shops, market halls, cafés and restaurants. In response to the commercial changes witnessed during the late twentieth century, these protective measures—classification or inscription—aimed above all at preserving the shopfronts and interior designs dating from the turn of the nineteenth and twentieth centuries, elements characteristic of their period. But historic monument protection of the tangible heritage has not meant, however, that the original commercial activity has always been maintained, and many of the protected establishments have closed down or been transformed. In the same way, if the protective measures give proper recognition to the artistic and historic interest of the places, they have not made them into museums and have not necessarily preserved the memory of the commercial activity or the objects originally associated with this activity. Nonetheless, the study of this theme continues in the region and is now focusing on places dating from the first half of the twentieth century.